Peraturan Daerah Horison dalam Undang-Undang Nomor 1 Tahun 2022 (Tinjauan Yuridis Dana Kompensasi Penggunaan Tenaga Kerja Asing) - Indaryanto, Wisnu (Jurnal Legislasi Indonesia, 2022)
The impact of Law No. 1 of 2022 on Financial Relations between the Central Government and Regional Governments seems to be quite perplexing for Regional Governments. This is due to changes in the nomenclature of several user fees that are a source of revenue for the region. The levy on the use of foreign workers is one of them. A quo law also includes orders for an omnibus law regional regulation in terms of regional taxes and levies, as well as a horizon regional regulation. A horizon regulation is a regional regulation whose validity period is limited or whose validity period is known at the time it is formed. This study uses a normative legal research method with a statutory and conceptual approach. The conclusion of this paper is the formation of a Perda Horizon by the Regional Government as a consequence of Law No. 1 of 2022.